Importance of glucose 6 phosphate dehydrogenase (G6PD) status in the management of methaemoglobinaemia - Mohd Tohit, Eusni Rahayu; Nallappan, Geetha; Idris, Faridah; Mustapha, Siti Zubaidah; Abdul Hamid, Hanisah (Universiti Putra Malaysia Press, 2024)
Methylene blue is an antidote for methaemoglobinaemia, but it is not given to individuals with glucose 6 phosphate dehydrogenase (G6PD) deficiency since it could potentially worsen oxidative haemolysis. We report the case of a 36-year-old male with unknown G6PD status who presented with oxidative haemolysis and methaemoglobinaemia. The fluorescence spot test showed a normal G6PD level. Methylene blue was given, but it was stopped as his anaemia worsened with no improvement in methaemoglobin level. This case highlights the challenges in the management of methaemoglobinaemia with concurrent oxidative haemolysis when the G6PD status of the patient is not known. In the acute presentation of oxidative haemolysis, molecular tests to detect G6PD deficiency can be time consuming and fluorescent spot test could give a false negative result. Therefore, it is highly advisable to avoid methylene blue for patients with unknown G6PD status when they have concurrent oxidative haemolysis and methaemoglobinaemia.